The untapped potential of targeting NRF2 in neurodegenerative disease - Chen, Wei-Tai; Dodson, Matthew (Frontiers in Aging, 2023)
Since its initial discovery almost three decades ago, the transcription factor nuclear factor erythroid 2-related factor 2 (NRF2) has been shown to regulate a host of downstream transcriptional responses and play a critical role in preventing or promoting disease progression depending on the context. Critically, while the importance of proper NRF2 function has been demonstrated across a variety of pathological settings, the ability to progress NRF2-targeted therapeutics to clinic has remained frustratingly elusive. This is particularly true in the case of age-related pathologies, where NRF2 is a well-established mitigator of many of the observed pathogenic effects, yet options to target this pathway remain limited. Along these lines, loss of NRF2 function has clearly been shown to enhance neuropathological outcomes, with enhancing NRF2 pathway activation to prevent neurodegenerative/neurological disease progression continuing to be an active area of interest. One critical obstacle in generating successful therapeutics for brain-related pathologies is the ability of the compound to cross the blood brain barrier (BBB), which has also hampered the implementation of several promising NRF2 inducers. Another limitation is that many NRF2 activators have undesirable off-target effects due to their electrophilic nature. Despite these constraints, the field has continued to evolve, and several viable means of targeting NRF2 in a neuropathological context have emerged. In this perspective, we will briefly discuss the key findings and promising therapeutic options that have been discovered to date, as well as highlight emerging areas of NRF2-neurodegeneration research that provide hope for successfully targeting this pathway in the future.